2020
DOI: 10.1038/s41577-020-00446-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of memory B cell differentiation

Abstract: During an immune response, B cells that encounter their cognate antigen become activated and differentiate to form short-lived antibody-secreting cells or germinal centre (GC)-independent memory B cells (MBCs). Within the GC, B cells engage with antigen and compete for limiting amounts of T cell help, which is necessary for B cell survival, proliferation and eventual differentiation into plasma cells or GC-derived MBCs 1. The GC is also the primary site in which B cells undergo somatic hypermutation, with B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 163 publications
(278 reference statements)
8
172
0
Order By: Relevance
“…Analysis of BCR repertoires and transcriptomes revealed that the highest levels of SHM and Ig class-switching occurred in the memory B cell subset. This finding is consistent with the generation of germinal center-derived memory B cells following antigen encounter 61,62 . Similarly, SHM and Ig class-switching levels were directly correlated with B cell clonal expansion.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of BCR repertoires and transcriptomes revealed that the highest levels of SHM and Ig class-switching occurred in the memory B cell subset. This finding is consistent with the generation of germinal center-derived memory B cells following antigen encounter 61,62 . Similarly, SHM and Ig class-switching levels were directly correlated with B cell clonal expansion.…”
Section: Discussionsupporting
confidence: 89%
“…A transcription factor, hematopoietically-expressed homeobox protein (Hhex) that is expressed in MBC precursors and promotes MBC differentiation ( 50 , 90 ) can interact with cMyc to decrease its activity, including cell proliferation and metabolism in tumors ( 96 ). Reception of differential signals for positive selection induces these transcription factors at varied levels in positively selected GC-B cells ( 97 ), which most likely play a part in MBC differentiation. However, the overall nature of the signaling network for transition from GC-B cell to MBCs remains unknown.…”
Section: Molecular Events During Positive Selection and B Cell Fate Imentioning
confidence: 99%
“…These terminally differentiated effectors, can reduce the duration of infection and decrease morbidity and mortality (Lee et al, 2011). The cues that direct memory B cells toward this early protective effector PB fate and the relationship between effector-like memory B cells and other durable GC-derived or extrafollicular memory B cell populations are not well understood (Laidlaw and Cyster, 2020).…”
Section: Introductionmentioning
confidence: 99%